Smart City-Based Public Service Innovation at the Investment and One-Stop Integrated Services Office of Palangka Raya City - Syamsuri, Syamsuri; Puspita Ayu, Katriani; Agusta Sahay, Marvy Ferdian; Cahya Wulandari, Dwi Asri (Iapa Proceedings Conference, 2024)
This study examines the diffusion of digital-based public service innovations at the Department of Investment and One-Stop Integrated Services (DPMPTSP) in Palangka Raya City, Indonesia. Utilizing Everett M. Rogers' Diffusion of Innovation theory, the research analyzes the implementation of three online service applications: SIMYANDU, OSS-RBA, and SIMBG. These applications, launched in 2021, aim to enhance public service delivery by offering online access to various administrative procedures, including permit applications, business registration, and investment licensing. The study investigates the effectiveness of DPMPTSP's communication strategies in promoting these services, the timeline of their adoption by the public, and the inclusivity of access to these digital tools. Findings highlight the successful integration of these applications into the public service landscape of Palangka Raya City, contributing to the development of a smart city. The study also explores the implications of these innovations for improving government service delivery and citizen engagement in the digital age.